Assessment of Disproportionate Costs in Environmental Policy with a Special Focus on Water Management - Macháč, Jan (2018)
The dissertation deals with application of economic approaches in water management. The thesis focuses on the principle of disproportionate costs and the EU Water Framework Directive (Directive 2000/60 EC). The Directive has a major impact on water management and national economy and contains numerous requirements, including “good status” of all water bodies. However, achieving this environmental target is connected with large investments, often beyond polluters’ capabilities. In justified cases, member states may request an exemption. Disproportionate costs of meeting the Water Framework Directive requirements can be used as a reason for extending the deadline for achieving the “good status” or reducing the desired goal. Nevertheless, the Directive grants a relatively high level of discretion relating to the definition of the cost proportionality. The Directive implies the need for application of economic analysis. The objective of the thesis is to discuss the different approaches used abroad, to test the methods in the Czech Republic’s context and to provide recommendations for application of cost disproportionality analysis. The thesis puts a special emphasis on complementary methods that can be applied in planning in water management from the economic point of view to achieve the “good status”. The dissertation is designed as a cumulative thesis composed of accepted articles/article in the review process in international journals with impact factor/in peer-reviewed international conference proceedings indexed in the Web of Science. The results of the five scholarly articles show that cost-benefit analysis seems to be an appropriate approach to cost disproportionality analysis, which can be combined with other methods such as cost-effectiveness analysis, Bayesian networks or game theory. However, calculation of benefits and costs of measures brings several methodological complications and uncertainties.